DASH Diet Concordance Among Adults in the Mediators of Atherosclerosis in South Asians Living in America (MASALA) Study (2010–2013). (7th June 2021) - Murphy, Bridget; Talegawkar, Sameera; Kanaya, Alka; Deierlein, Andrea; Gadgil, Meghana; Kandula, Namratha; O'Connor, Joyce; Parekh, Niyati
Abstract: Objectives: South Asian Americans have a disproportionately higher risk of atherosclerotic cardiovascular disease (ASCVD) and risk factors, such as hypertension compared to non-Hispanic whites and other Asian American groups. Our objective was to investigate adherence to Dietary Approaches to Stop Hypertension (DASH), an established dietary pattern to reduce blood pressure, and association with sociodemographic, body composition, and ASCVD risk factors. Methods: Baseline data from 893 adults (40–83y, 47% female) recruited between 2010–2013 for the MASALA Study were used in these analyses. We computed a DASH concordance score from the validated 163-item Study of Health Assessment and Risk in Ethnic groups food frequency questionnaire (FFQ), using an established method. We scored concordance based on 8 components: high intake of 1 ) fruit, 2 ) vegetables, 3 ) nuts/legumes, 4 ) low-fat dairy products, and 5 ) whole grains, and low intake of 6 ) sodium, 7 ) sugar-sweetened beverages, and 8 ) red/processed meats. The theoretical DASH score may range from 8 (low concordance) to 40 (high concordance). Results: The DASH score in MASALA participants ranged 12–35 (mean ± SD, 24.4 ± 4.4). The average score was higher among women (25.4 ± 4.1) than men (23.6 ± 4.5; P < 0.001), higher among adults 65 and older than those ≤50 (24.9 ± 4.3 vs. 23.9 ± 4.6, P = 0.015), and higher among participants who had lived less than 50% of their life in the U.S. (24.9 ± 4.4 vs. 23.9 ± 4.4, p-0.0014). The score was also higher among participants who had a Bachelor's degree or greater ( P = 0.0064), but there was no difference in the score based on annual family income ( P = 0.07). The score was higher among vegetarians than non-vegetarians (26.7 ± 3.5 vs. 23 ± 4.4; P < 0.001). It was also inversely associated with indicators of central adiposity including waist circumference ( P = 0.001) and waist-to-hip ratio ( P < 0.001). Conclusions: Our results indicate that adherence to the DASH dietary pattern is associated with select sociodemographic factors and body composition among South Asians in the U.S. The computed DASH score will be utilized in forthcoming analyses to determine its associations with risk factors for hypertension, central adiposity, and ASCVD among participants in the MASALA cohort. Funding Sources: NHLBI, National Center for Research Resources, National Center for Advancing Translational Sciences, NIH, via UCSF-CTSI.